A probe into the Philippines' potential for cross-cultural psychological research the view from early socialization findings - Del Pilar II, Gregorio H. (Philippine Journal of Psychology, 1980)
Works on 11 Philippine ethnic groups were examined to determine whether sufficient, non-trivial differences exist among these groups' early socialization practices. This was aimed at probing into the Philippines' potential for cross-cultural psychological research. Three general findings having to do with 1) the sharing by parents in the disciplining of children other than their own in Philippine rural communities; 2) use and non-use of corporal punishment; and 3) differences of the Maranao ethnic group from the others on maratabat, a fierce pride in one's family identity, a segregation of sexes, and mother-child sleeping arrangements were found. Possible sources of error were identified and research indications noted. These findings were interpreted to be indicative of some potential in the Philippines for cross-cultural psychological research.